Social and economic life in Elam from the beginning of the third millennium until the mid of the second millennium BC - عبود, جهاد; سليمان, صبا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
By looking at the civilizational history of the ancient Western Asia in general, the Iranian plateau and its relationship with the Mesopotamian region, some information can be obtained about the ancient man who inhabited Elam. The study of social life in Elam and its comparison with the social life of the people of Mesopotamia illustrates the nature of the Elamite society, its ethnic composition, culture, and civilizational connection with other ancient peoples in the ancient world, in the third millennium B.C., which was reflected in the life of Elamite in various aspects of life.